Радзивіллівські володіння новітніх часів очима сучасників - Русина, О.В. (Український історичний журнал, 2014)
Ідеться, головним чином, про опис радзивіллівських володінь авторства відомого
польського письменника XIX ст., чиє життя було нерозривно пов’язаним з
Україною – Ю.Крашевського. Окрім поданого ним опису Олики – міста на Волині,
що впродовж чотирьох століть належало Радзивіллам, аналізуються також
нотатки про побут представників цієї родини на рубежі ХІХ–ХХ ст., котрі залишив
М.Радзивілл. Публікація містить зроблений Ю.Крашевським у 1856 р. й
досі невідомий українському загалу малюнок Олицького замку. The paper deals mostly with the description of Radziwiłłs’ estates made by famous Polish
writer J.Kraszewski whose life was inseparably connected with Ukraine. The most remarkable
of Ukrainian cities owned by Radziwiłłs was Olyka (Volyn’ region) which constituted
family’s property for four centuries. Along with its description by Kraszewski, the
paper examines notes about Radziwiłłs’ living there on the verge of 19–20th centuries left
by M.Radziwiłł. The article also contains Kraszewski’s drawing of local castle (1856) still
not known to Ukrainian audience.